Experiences of healthcare interactions before and after suicidal behaviour among older adults attending geropsychiatric services: an interpretative phenomenological analysis - Margda Waern; Maja Sjöberg; Sara Hed; Stefan Wiktorsson; Anne Ingeborg Berg; Jennifer Strand; Sabrina Doering (BMJ Open)
Objectives Physical illness and functional disability are common in older adult populations and strongly linked to suicidal behaviour. The aim was to explore how older adults who engaged in a suicidal act experienced their interactions with healthcare providers.Design This study re-examined transcripts from a broader study involving experiences of older adults who took part in two separate semi-structured interviews focusing on their experiences before and after a suicidal act. Interpretative phenomenological analysis was applied.Setting A geriatric psychiatric outpatient clinic in a large Swedish city.Participants Participants (70+) were recruited among consecutive Swedish-speaking patients in outpatient treatment following a suicidal act within the last 3–36 months. Exclusion criteria were personality disorder, ongoing psychosis, aphasia, delirium, clinical dementia or Montreal Cognitive Assessment score indicating moderate/severe cognitive impairment. Out of 22 eligible, nine accepted participation (four women and five men, age range 71–92 years). Prior to the suicidal act, all had their main care contact in primary care, and all but one were on antidepressants.Results Participants described interactions with healthcare services that amplified their feelings of alienation, loneliness, worthlessness and self-stigma. Difficulties accessing care increased their sense of powerlessness. Some participants were cognizant of their mental health needs but experienced obstacles that hindered them from managing their illness, which reduced their sense of agency. These situations increased frustration and hopelessness and contributed to the development of suicidal behaviour. On the contrary, feeling listened to in trustful and validating relationships helped restore self-respect and agency and fostered engagement in their individual suicide preventative strategies.Conclusions The findings can inform educational interventions and clinical approaches to the care and management of older adults with symptoms of common mental disorders. Exploring experiences of care interactions before and after suicidal acts across different clinical settings and cultures could be areas for future research.